1996
DOI: 10.1093/genetics/142.4.1069
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the PUT3 Transcriptional Activator of the Proline Utilization Pathway in Saccharomyces cerevisiae

Abstract: Proline can serve as a nitrogen source for the yeast Saccharomyces cerevisiae when preferred sources of nitrogen are absent from the growth medium. PUT3, the activator of the proline utilization pathway, is required for the transcription of the genes encoding the enzymes that convert proline to glutamate. PUT3 is a 979 amino acid protein that constitutively binds a short DNA sequence in the promoters of its target genes, but does not activate their expression in the absence of induction by proline and in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Furthermore, in S. cerevisiae , proline degradation can activate the PUT3 transcription factor [ 45 ]. PUT3 regulates the other two proline-regulating genes, PUT1 and PUT2, and can also positively control the riboflavin transporter MCH5 [ 46 ]. In the present study, transcriptome comparison revealed that the homologous genes of PUT3 and FlMCH5 in yellow mushrooms were Unigene2188_All and CL911.Contig3_All, respectively, and that these two transcripts were only expressed in yellow mushrooms and not in white mushrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in S. cerevisiae , proline degradation can activate the PUT3 transcription factor [ 45 ]. PUT3 regulates the other two proline-regulating genes, PUT1 and PUT2, and can also positively control the riboflavin transporter MCH5 [ 46 ]. In the present study, transcriptome comparison revealed that the homologous genes of PUT3 and FlMCH5 in yellow mushrooms were Unigene2188_All and CL911.Contig3_All, respectively, and that these two transcripts were only expressed in yellow mushrooms and not in white mushrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Because the aromatic amino acids are the inducers of Aro80p, the same activation mechanism might be conserved, but a direct interaction has not been demonstrated yet (Lee and Hahn, 2013). The substitution G 532 R in Put3p impairs the activation by proline without affecting the activity of other domains but an additional R 764 T substitution not just recovers but increases the activity of Put3p, which becomes proline insensitive (Ann des Etages et al, 1996). Other substitutions in the middle region have an impact on the AD masking which could produce either a permanent or loose unmasking that increases the transcription activity (Kohlhaw, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Activators have two essential domains: a DBD and an AD . Factors that contribute to the pool of activator proteins that are available to regulate transcription include mp interactions, aggregation, target/coactivator binding, and proteolysis .…”
mentioning
confidence: 99%
“…Natural ADs are unstructured in solution and have a characteristic "stickiness" that results in a promiscuous binding profile; they have been shown in vitro to interact with both transcriptionally relevant and unrelated proteins with moderate affinity . As part of a complex signaling network, there are masking proteins (mp) that shield activation domains from non-productive binding interactions until they are required for gene expression (Figure ) . An excellent example of this is the mouse homolog of double minute 2 (hDM2), a masking protein that regulates p53 function by discriminating p53-coactivator interactions and playing a role in p53 turnover .…”
mentioning
confidence: 99%
See 1 more Smart Citation